Towards an Analysis of the Visual Images of the Drawings of the Child Survivors of War: A Semiotic Study - Alaminah R. Abdussalam (RIRAI Publisher, 2024)
In this research, children used poster narratives to communicate their perspectives of the Marawi Siege. A social semiotic approach was utilized to understand their visualizations. This study aimed to look into the aspect of understanding the narratives of the child victims of the Marawi Siege through their drawings, referred to poster narratives in this study, by extracting the visual images present. The collection of data was limited to the two temporary shelters in Marawi: Boganga and Rorogagus. The researcher collected 40 poster narratives from the different temporary shelters in Marawi City, and the recurrent visual images were those of Social Actors, Shattered Place, Battle Aircraft and Weapons. The child-respondents included significant minute details in illustrating the social actors such as tears, sad and scared expressions, color and position, and at times, supported these emotions with texts which served as anchorage. From these findings, it could be drawn that a careful study of the shapes, strokes, colors, position, number and size of the images was of paramount significance to better understand the data output of the children-respondents. The posters are not meaningless forms or shapes. They convey materials or images from the deeper recesses of the minds or psyches of the respondents.